Pathogenesis and Clinical Features of Fungal Keratitis (Review) - K. I. Belskaia; A. S. Obrubov (Oftalʹmologiâ, 2021)
In this review we presented the information about pathogenesis of mycotic keratitis and the most characteristic clinical signs that can help ophthalmologists to suspect mycotic etiology. In conditions of poor accessibility and informativeness of laboratory and instrumental diagnostic tests, the analysis of the anamnesis and the clinical signs remain the only information that can be used by a physician while making a diagnosis and choosing treating strategies. This review contains the results of a number of studies. In the review we show the progression phases of cornea mycotic infection, among them adherence, invasion, morphogenesis and toxigenicity. We also reveal that the most characteristic clinical signs of mycotic keratitis are scalloped rough edge of stromal defect, prominent dry crumby or caseous structured view of infiltrates and necrotic masses, satellite infiltrates, certain changes of color of the defected area. Heaviness of mycotic keratitis ulcer defect has a correlation with an unfavourable prognosis for disease. Mycotic keratitis during contagion can be complicated by mycotic glaucoma with a malignant disease course and endophthalmitis. There can be cases with mixed infection. While Almost No clinical sign is pathognomonic for keratomycoses, summing up all the signs can verify the diagnosis. Ophthalmologists need training in the recognition the clinical signs of infectious keratitis. Also new methods of fast diagnostics of infectious keratitis etiology and implementation on a large scale are needed.